Head Impact Exposure in Junior and Adult Australian Football Players - Hecimovich, Mark; King, Doug; Dempsey, Alasdair; Murphy, Myles (Wiley, 2018)
This study measured and compared the frequency, magnitude, and distribution of head impacts sustained by junior and adult Australian football players, respectively, and between player positions over a season of games. Twelve junior and twelve adult players were tracked using a skin-mounted impact sensor. Head impact exposure, including frequency, magnitude, and location of impacts, was quantified using previously established methods. Over the collection period, there were no significant differences in the impact frequency between junior and adult players. However, there was a significant increase in the frequency of head impacts for midfielders in both grades once we accounted for player position. A comparable amount of head impacts in both junior and adult players has implications for Australian football regarding player safety and medical coverage as younger players sustained similar impact levels as adult players. The other implication of a higher impact profile within midfielders is that, by targeting education and prevention strategies, a decrease in the incidence of sports-related concussion may result.
Keywords: 42 Health Sciences; 4207 Sports Science and Exercise; Traumatic Head and Spine Injury; Traumatic Brain Injury (TBI); Neurosciences; Brain Disorders; Physical Injury - Accidents and Adverse Effects; 4207 Sports science and exercise